(untitled) (Singapore, 2004)
This volume concerns the latest results on pulsed plasma production by energetic laser pulses irradiating solid targets. The produced plasma emits neutrals, clusters, ions, electrons and photons. Plasma properties depend on the laser pulse duration, energy, wavelength, focusing, target nature and irradiation conditions. Plasma expands in vacuum with supersonic velocity and may accelerate heavy ions, with charge states higher than 50+, at energies higher than 10 MeV. This book presents and discusses possible applications, such as ion injection in ECR ion sources, ion implantation, ion post-acceleration and thin film deposition by the PLD technique.
Keywords: Plasma engineering,Laser ablation,Kỹ thuật Plasma,Laser cắt